A superior electronic conducting tellurium electrode enabled high rate capability rechargeable Mg batteries. (September 2020) - Lu, Tao; Zhang, Zhonghua; Chen, Bingbing; Dong, Shanmu; Wang, Chengdong; Du, Aobing; Wang, Longlong; Ma, Jun; Cui, Guanglei
Abstract: Magnesium batteries are recognized as a potential alternative to lithium ion batteries benefited from the advantages of low cost, high safety, and high energy density. But the development of magnesium batteries suffers from the sluggish motion of Mg 2+ in solid electrodes due to strong polarization. Compounds explored to accommodate magnesiation/demagnesiation, suffer from low capacity, sluggish kinetics and poor cycling performance. In this manuscript, copper current collector aided tellurium (Te) as the cathode material of magnesium battery is proposed. Due to superior electronic structure of Te atom, both reactants and products of cathode reaction exhibit metallic conductivity which accelerates the magnesiation/demagnesiation process This material delivers a specific capacity of 338 mAh/g at 100 mA/g, and keeps at 178.5 mAh/g after 400 cycles. Moreover, the electrode performs superior rate capability than the previously reported materials. A specific capacity of 265.4 mAh/g is achieved at 2 A/g without obvious polarization. Even at a very high current density of 3.75 A/g, a specific capacity of 118 mAh/g is still maintained. This study highlights the importance of electronic structure for multi-valent ion reaction related material, which also offers new strategy for cathode design of Mg batteries. Graphical abstract: Image 1 Highlights: Tellurium (Te) based material is explored as the cathode of magnesium battery for the first time. Te based cathode for Mg battery exhibits the best rate capability up to date. Low migration energy of Mg 2+ in Cu2 Te, and weak Mg-Te, Cu-Te bonds due to the structure of Te, lead to high rate capability.